John F. C. Turner: vida, obra sua contribuição para a revisão da política habitacional nos anos 1970 - Zylbersztajn, Breno Eitel (2018)
The purpose of this paper is to understand the formation, professional performance and ideology of urban planner John F. Turner and to elucidate the direct and indirect contribution of the urban planner to the formulation of low cost housing policies, programs and projects during the 1970s in São Paulo. In order to do so, a cross-section is made in the history of the urban planner Turner, object of this research, from the period of his academic formation to the consultancy given to the municipality of São Paulo in the project conducted by the IPT, Habitat Guidelines (1977). When analyzing the path of an ideology in the formulation of public policies, we intend to demonstrate the reference of urban planner Turner in the science of urbanism in São Paulo. Therefore, as a cut, the research focuses on the formation, professional performance and consulting of urban planner John F. C. Turner in São Paulo (1977). I consider this work the introduction to a field of research on the rise, which would be the participation of the beneficiaries in projects of urbanization of favelas and housing projects.